2017
DOI: 10.1038/s41598-017-17089-4
|View full text |Cite
|
Sign up to set email alerts
|

Mouse papillomavirus infection persists in mucosal tissues of an immunocompetent mouse strain and progresses to cancer

Abstract: Mouse papillomavirus has shown broad tissue tropism in nude mice. Previous studies have tested cutaneous infections in different immunocompromised and immunocompetent mouse strains. In the current study, we examined mucosal infection in several immunocompetent and immunocompromised mouse strains. Viral DNA was monitored periodically by Q-PCR of lavage samples. Immunohistochemistry and in situ hybridization were used to determine viral capsid protein and viral DNA respectively. All athymic nude mouse strains sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 43 publications
6
67
0
Order By: Relevance
“…Oral swabbing and detection of MmuPV1 by PCR. The method for detecting the MmuPV1 E2 gene in oral swab samples by PCR was adapted and modified from previously reported work (29,32). Briefly, tongues of anesthetized mice were drawn out by forceps, and the infection sites were swabbed multiple times using a flat toothpick.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral swabbing and detection of MmuPV1 by PCR. The method for detecting the MmuPV1 E2 gene in oral swab samples by PCR was adapted and modified from previously reported work (29,32). Briefly, tongues of anesthetized mice were drawn out by forceps, and the infection sites were swabbed multiple times using a flat toothpick.…”
Section: Methodsmentioning
confidence: 99%
“…While initially found to cause cutaneous warts in immunodeficient mice, MmuPV1 also causes cutaneous warts in immunocompetent strains with or without alterations to their immune system (19,(22)(23)(24)(25)(26)(27). Importantly, MmuPV1 has a wide tissue tropism: it infects not only cutaneous epithelia but also sites typically implicated in the sexual transmission of HPV, including the mucosa of the female and male genitalia, the anus, and oropharyngeal sites (28)(29)(30)(31)(32)(33)(34). We have previously shown that immunocompetent mice experimentally infected with MmuPV1 in their female reproductive tract developed cervical and vaginal cancers (28), much like high-risk HPVs in humans.…”
mentioning
confidence: 99%
“…These limitations have been overcome by the discovery of the mouse papillomavirus, MmuPV1 or MusPV1, in 2011 [14], the first papillomavirus discovered to infect laboratory mice (Mus musculus). We and others found that MmuPV1 can be used to model infection by high-risk HPVs: 1) MmuPV1 and HPVs encode a similar set of genes and express similar patterns of viral transcripts [15,16]; 2) like HPV, MmuPV1 E6 and E7 genes both play critical roles in pathogenesis [17,18] (manuscript in preparation); 3) MmuPV1 preferentially causes disease in immunocompromised hosts [19][20][21][22] as observed for HPVs in humans; and 4) persistent viral infections lead to cancer in both cutaneous and mucosal sites [20,[23][24][25]. Prior studies of MmuPV1 infection in immunocompetent FVB/N mice showed that persistence of cutaneous papillomas correlated with an immunosuppressive state [20].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the association of HPV as the signature pathogen in WHIM syndrome is unusually strong for a primary immunodeficiency disease. Host species specificity makes it quite difficult to study the immunology of HPV; however, the discovery of a mouse papillomavirus known as MusPV or MmuPV1, which has wide tissue tropism, is likely to provide useful clues for understanding HPV pathogenesis . Development of highly effective prophylactic vaccines that induce strong humoral immunity that blocks initial infection are currently focused on genital types but have become universally recommended in developed countries to prevent anogenital cancer that is particularly likely to develop if infection with high‐risk HPV such as types 16 and 18 are not cleared.…”
Section: Wartsmentioning
confidence: 99%
“…Host species specificity makes it quite difficult to study the immunology of HPV; however, the discovery of a mouse papillomavirus known as MusPV or MmuPV1, which has wide tissue tropism, is likely to provide useful clues for understanding HPV pathogenesis. [30][31][32] Development of highly effective prophylactic vaccines that induce strong humoral immunity that blocks initial infection are currently focused on genital types but have become universally recommended in F I G U R E 2 WHIM syndrome genetics. The crystal structure of CXCR4 complexed with a small molecule isothiourea derivative antagonist (structure CXCR4-2/IT1t1; PDB ID# 3ODU) is shown to the left with red asterisks designating the locations of mutations that cause WHIM syndrome.…”
Section: Wa Rtsmentioning
confidence: 99%